Strengthening Early Childhood Teachers’ Competence through Professional Learning Communities in Rural Indonesia - Rusmiyati Rusmiyati; Wiwik Pudjaningsih (Universitas Kristen Satya Wacana, 2026)
This study examines how a cluster-based Professional Learning Community (PLC) strengthens early childhood teachers’ competencies in a rural Indonesian context. Employing a qualitative case study design, data were collected through semi-structured interviews with 12 participants (8 teachers, 2 coordinators, and 2 principals), non-participant observations of 4 PLC meetings, and document analysis of lesson plans and meeting records. Thematic analysis revealed that the Anggrek Cluster functions as a collaborative learning infrastructure that enhances pedagogical competence through joint lesson planning, reflective dialogue, and peer feedback. Participation in the PLC fostered adaptive instructional practices, diversified teaching strategies, and clearer alignment between learning objectives and classroom implementation. The findings also indicate the emergence of collective teacher efficacy, as participants increasingly framed instructional challenges as shared professional responsibilities. Despite contextual constraints such as limited resources and meeting frequency, trust-based collaboration and distributed leadership enabled sustained engagement. This study contributes to PLC scholarship by extending empirical evidence to a rural early childhood setting in a developing country and highlighting the mediating role of collaborative inquiry and collective efficacy in competency development. The findings suggest that cluster-based PLCs can serve as contextually sustainable professional development mechanisms in resource-constrained environments.